GUIDELINES TO DEVELOP THE EDUCATION ADMINISTRATIVE QUALITY OF BUDDHIST WAY SCHOOL ADMINISTRATORS IN KLONGLUANG DISTRICT PATHUMTANI PROVINCE - Hanphala, Chitsanuphum; PhrakhruKittiyanawisit; PhrakhuOpatnontakitti (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims: 1) to study the quality of educational management of Buddhist school administrators, 2) to study the methods for developing the quality of educational management of Buddhist school administrators, and 3) to propose a guideline for developing the quality of educational management of Buddhist school administrators. This research was conducted using a mixed-methods method. The quantitative research used a questionnaire with a sample of 277 school administrators and teachers. Data were analyzed using statistics including mean and standard deviation, and the qualitative research conducted by interviewing 5 key informants. The results of the research found that: 1) Overall, the opinions on the quality of educational management of Buddhist school administrators were at a high level. When considering each aspect, the opinions were at a high level in all 4 aspects, namely, impact/feedback, input factors, output, and process, respectively. 2) The methods for developing educational management of Buddhist school administrators consisted of (1) input factors: precepts; Administrators, teachers, and students must have a way of life that was consistent with the principles of Buddhism, observed the 5 precepts, and behaved as a good example, meditation was the development of mind control, training the mind to be balanced, wisdom was the understanding and use of experience in making decisions and behaving in daily life mindfully. (2) Process: Morality; Executives, teachers, and students organizing integrated learning activities, integrating Buddhist principles into learning and applying them in daily life. Meditation; Executives, teachers, and students could develop themselves to be careful, analytical, and problem-solving. Wisdom; Promoting good relationships, encouraging everyone to participate, and seeing the value in preserving and continuing Buddhism. (2) Output: Morality; Executives, teachers, and students should be disciplined, responsible, punctual and grateful. Meditation; Executives, teachers, and students consumed the four necessities in appropriate quantities and quality, and lived a life that benefited the environment. Wisdom; Having faith and correct understanding of the Triple Gem, being eager to learn, seeking the truth, and being creative. (3) Impact/Repercussions: Morality was related to the framework of the Buddhist philosophy. Meditation; Analyzing and evaluating the results of good and sustainable activities for the school and community. Wisdom; Making a backup operation plan and preparing for readiness. And 3) Guidelines for developing the quality of education management for Buddhist school administrators, consisting of (1) Input factors, in terms of inputs, administrators must be good friends, being good role models to teachers, students and the community, having faith in Buddhism and living their lives by Buddhist principles. In terms of management, clear vision, goals and missions were set, continuous monitoring and evaluation was provided, and the school atmosphere was shady, clean and safe, and far from vices. (2) In terms of process, integrated teaching and learning with Buddhist principles was organized so that students could apply them in their daily lives, promoting students to be excellent and happy, and living their lives based on the Tri-Sikkh principle (Threefold Learning). (3) In terms of outputs, morality, mind and wisdom were developed to be clear and tangible, knowing oneself to live life based on correctness, living with the environment sustainably, being grateful, having a beautiful mind and having faith in Buddhism. (4) In terms of impacts/backlash, implementation was carried out according to the framework of home, temple and school, keeping the precepts, promoting faith and belief in Buddhism, working in steps and systematically, analyzing and evaluating, and integrating management based on the Tri-Sikkh principle (Threefold Learning).